In vitro degradation behavior of a hydroxyapatite/poly(lactide-co-glycolide) composite reinforced by micro/nano-hybrid poly(glycolide) fibers for bone repair. Issue 44 (31st October 2017) - Zhu, Yuhang; Wang, Zongliang; Li, Linlong; Gao, Daqian; Xu, Qinli; Zhu, Qingsan; Zhang, Peibiao
Abstract : A poly(glycolide) (PGA) fiber-reinforced hydroxyapatite/poly(lactide- co -glycolide) (HA/PLGA) composite with high mechanical strength has been prepared previously. Abstract : A poly(glycolide) (PGA) fiber-reinforced hydroxyapatite/poly(lactide- co -glycolide) (HA/PLGA) composite with high mechanical strength has been prepared previously. In this paper, in vitro degradation of ternary composites with different contents of PGA fibers (0, 30, 50 and 70 wt%) was investigated. Water absorption showed a marked increase as the degradation progressed, and the composite with 70 wt% PGA fibers showed the highest final water uptake which was 3.89 times higher than the initial value. The mass loss of the composite with 70 wt% PGA fibers was 79.3 ± 6.47% at 16 weeks, which was the highest among all the composites. The molecular weight of the PLGA matrix decreased over time especially for the composites containing 70 wt% PGA fibers. The lowest pH of the buffer solution was also observed in the composite with 70 wt% PGA fibers. Environmental scanning electron microscopy (ESEM) and micro-computed tomography (micro-CT) results demonstrated that the porosity of the composites and the size of the pores gradually increased as the degradation progressed. The most significant change in compression strength was observed for the composite with 70 wt% PGA fibers which was reduced from an initial value of 20 MPa to approximately 1 MPa at 16 weeks. The results indicated that the in vitro degradation of the composites could be accelerated by increasing the content of PGA fibers. It implied that the ternary composites might be a candidate for the repair of non-load bearing or cancellous bone which needs high initial strength and fast degradation rate.